Borehole heat store design optimization - Nordell, Bo (Luleå tekniska universitet, Arkitektur och vatten, 1994)
Seasonal heat storage, which is used to balance the supply of and demand for heat, e.g. in district heating networks, is necessary for the large-scale utilization of solar heat. The aim of this thesis was to study and develop seasonal heat storage to a point where it, if possible, would be an option in Swedish heating systems. Initial theoretical calculations indicated that the borehole heat store was feasible for seasonal heat storage. In the borehole heat store sensible heat is stored in the bedrock. The bedrock is penetrated by evenly spaced vertical boreholes, which are drilled within a square or circular land area. The holes work as heat exchangers between a heat carrier (normally water), which is pumped through the pipe system of the boreholes and the storage volume. Performed measurements in a pilot plant verified the predicted thermal behaviour of the store. A pre-design of a large-scale heat store, within the University area, was performed. After assuming the operation cycle and the properties of the store, the thermal behaviour of the Luleå heat store was simulated. The construction work of this large-scale borehole heat store (120,000 m 3) was studied in detail and the performance was evaluated during the first five years of operation. It was found that there were several short-comings in design, construction and operation. The operation of the heat pumps caused problems. The borehole pipes were incorrectly installed, which decreased the charged heat by 23% and recovered heat by about 34%. Without changing the storage task the store could have been built at a cost of 4.5 MSEK instead of 6.3 MSEK. A model was developed to determine the optimum design of borehole heat stores. The optimum design was defined as the design that fulfils the storage task at a minimum annual storage cost, i.e. the sum of the annual costs of the investment, operation, maintenance and heat loss. The optimum and actual designs of three stores were evaluated and compared. The more recently constructed plants differed less from ...